(3EWGQgG GdacQj hJWHjbGJgG GdYdejIs - (3JjSjQ(B, (3GdeUQjs; (3WdGd LQjQI(B, s ((3YeGf(B:s (3OGQ GdKbGaI(B,s, 2006)
(3XghQ GdTQcGJ h eaghegG , GdeYGdLGJ GdeMGSHjI dJchjf TQcGJ GdJVGef h GdeYGdLGJ GdeJYdbI HMbhb GdTQcGA aj TQcGJ GdJVGef eY JYOjd YbO TQcI GdJVGef h GdMSGHGJ GdNJGejI h GdbhGFe GdeGdjI aj TQcGJ GdJVGef h JUajI TQcGJ GdJVGef h eMGSHI TQcGJ GdJhUjI GdHSjWI h CNjQG eMGSHI TQcGJ GdeMGUI (B.s
(3GdeQGLY U(B.511 ((3GbJfGAGJ (B2014 3(3f(B)s
Keywords: (3GdTQcGJs; (3GdeMGSHIs; (3eMGSHI GdTQcGJs